(untitled) (Zaporizhzhia Historical Review, 2021)
This article gives the description оf glass-handicrafts, found in late nomadic burials (IX – XIV centuries) of the Northern Black-Sea area. The author comes to the conclusion that the nomads rarely used the glassshandicrafts. Thу assortment of glasss goods is very limited and represented by beads, bangles and ornaments of clothes. In this region there was no case of discovering the glass goods in the graves. According to chemical composition the glass came to the nomads from different regions such as: Visantia, Kiev Russ, Caucasus, Central Asia, The Volga River region. This variegated picture reflects the mobile way of life of the nomads and their broad international and trade connections.